Routine tests for both planning and evaluating image quality in tele-echocardiography - Sandra Morelli; Andrea Giordano; Daniele Giansanti (Istituto Superiore di Sanità, 2009)
Both in real-time and "store & forward" tele-echocardiography (T-E), a coding process has to be applied to the echocardiography videoclips in order to limit the bandwidth needed and adapt it to the bandwidths furnished by network providers. The compression process degrades the videoclips, affecting thus the quality of the videoclips and potentially compromising the diagnostic accuracy of the T-E. In this work the authors investigated on the use of automatic tools for the video quality assessment by means of objective methods with particular care to the role of the system administrator. As the use of tests on video quality assessment (based on subjective methods) is hampered by the high number of needed resources (persons, laboratories and time). The use of valid objective methods is thus desirable. The study reviewed different tools with this specific aim. One of the more suitable tool was found to be represented by a software package designed by the Institute of Telecommunication Sciences and the National Telecommunication and Information Administration, the NTIA/ITS VQM tool. This tool gives back objective-quantitative data as outcomes, however embeds models emulating the subjective perception. This study reviewed and analyzed in depth the functionalities of the tool to improve the image quality in TE over the network. The tool was also found suitable for a more general process of T-E assessment, from a health technology assessment (HTA) perspective.